The Relevance Between Ability to Memorizing al-Qur'an and the Qira'ah Skills of Students at the Tahfidz Insan Mulia Punggur Islamic Boarding School| Keterkaitan Antara Kemampuan Menghafal al-Qur’an dan Keterampilan Qira’ah Santri Pondok Pesantren Insan Mulia Punggur - Salma Roidah; Siti Hamida; Widayanti, Rizka (An-nahdloh : Journal of Arabic Teaching, 2023)
The researcher conducted this study aiming to describe the relationship between the ability to memorize the Qur'an and the qira'ah skills of students at the Tahfidz Insan Mulia Punggur Islamic Boarding School. This type of research is descriptive qualitative research, data collection techniques were carried out using in-depth interviews and observations. The research instruments were female students and teachers of the Tahfidz Insan Mulia Punggur Islamic Boarding School. The results of this study indicate that there is a link between the ability to memorize the Qur'an and the qira'ah skills of female students at the Tahfidz Insan Mulia Punggur Islamic Boarding School. The level of ability to memorize the al-Qur'an is directly proportional to the ability of female students to improve qira'ah skills in learning, understanding, and reciting Arabic readings fluently and correctly. Vice versa, female students who master the correct and good qira'ah skills will find it easier to understand the content of the verses of the al-Qur'an as well as helping students memorize verses in the al-Qur'an.